Imagining socio-technical futures – challenges and opportunities for technology assessment. Issue 2 (4th May 2017) - Bechtold, Ulrike; Fuchs, Daniela; Gudowsky, Niklas
ABSTRACT: An increasing orientation of technology assessment (TA) and adjacent fields toward future socio-technological developments is leading scholars to examine, assess and adapt different approaches of future studies on various levels. In this special issue of the Journal of Responsible Innovation, a number of members of the extended TA community in Europe seek to advance different approaches to handling the unpredictable, to consider various possible socio-technical futures and to explore a more active role in technology design and shaping of the future as required by concepts such as responsible innovation (RI) or responsible research and innovation (RRI). The three German words 'Zukunft Macht Technik' (the title of a TA conference in Vienna in 2015) make a nice little pun in German: they can either be interpreted as the short sentence 'Future shapes technology' or as the assembly of the three nouns 'future power technology.' Both readings are borne in mind in this special issue. A main insight of this special issue is that we need to explore how the debate on imagined socio-technical futures is enriched by concepts such as R(R)I, taking into account that no future can exist without an awareness of the present setting of innovation processes and technology development.